Optimizing Motor Vehicle Inspection Services in Klaten to Improve User Access Through Quality Service - Olyvetrisia Olyvetrisia; Nerys Lourensius (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze and optimize the service system at the Motor Vehicle Inspection Division of the Transportation Agency in Klaten Regency. The method employed is a qualitative approach, which includes in-depth interviews, direct observations, and document studies. The findings indicate that approximately 70% of users complain about excessive waiting times, while 60% express dissatisfaction with the quality of service. Additionally, complicated procedures and a lack of clear information contribute to user dissatisfaction. To address these issues, the study recommends implementing an online registration system and a mobile application to enhance efficiency and transparency. Improving communication and information dissemination to users, along with continuous training for staff, is also deemed crucial for enhancing service quality. With these measures, it is expected that the Transportation Agency can meet public expectations and create a better user experience. This research contributes to the development of public policies that are more responsive to community needs